The politics and micro-politics of professionalization : an ethnographic study of a professional NGO and its interface with the state - McCusker, Monique (Stellenbosch : Stellenbosch University, 2008)
Thesis (MPhil (Sociology and Social Anthropology))--Stellenbosch University, 2008.